PENGARUH KONSERVATISME TERHADAP EARNINGS RESPONSE COEFFICIENT (ERC) (Students' Journal of Accounting and Banking, 2013)
This study aimed to examine the effect of accounting conservatism on earnings response coefficient (ERC), which accounting conservatism is explained by several components that have a relationship with conservatism. The components are then diijadikan a variable to test its effect on the ERC. So the independent variables in the study include discretionary accruals, debt covenants, growth opportunities and firm size. Meanwhile, the dependent variable is the ERC. This study used a sample of manufacturing firms listed on the Indonesia Stock Exchange (IDX) year observation period 2008-2011. Data were collected using purposive sampling method in order to obtain a sample of 160 companies. This study uses multiple regression analysis to data analysis. Results from the study showed discretionary accruals, debt covenants, and growth opportunities are not effect the ERC. Meanwhile, company size significant positive effect on the ERC. Keywords: Earning Response Coefficient, Discretionary Accruals, Covenant Debt, Growth Opportunities and Company Size.